Vascular cognitive impairment associated with NOTCH3 Exon 33 mutation: A case report. Issue 34 (August 2019) - Sun, Yong; Wei, Yan-Jun; Xing, Ying
Abstract: Rationale: Vascular cognitive impairment (VCI) is a common cause of dementia. Research suggests that hereditary factors (gene mutations) play an important role in the pathogenesis of VCI, and a mutation of the NOTCH3 locus is frequently identified in affected patients. Herein, we report the case of a patient with confirmed VCI associated with a NOTCH3 exon 33 gene mutation and review the relevant VCI literature. Patient concerns: A 48-year-old man presented to our neurology clinic with gradually progressive cognitive impairment. Diagnoses: Brain magnetic resonance imaging revealed multiple punctate hyperintensities in the patient's periventricular white matter. Genetic analysis showed a c.6744C > T, p. Ala2223Val substitution in exon 33 of the NOTCH3 gene. We diagnosed thepatient with VCI secondary to a NOTCH3 gene mutation. Interventions: Donepezil (5 mg) and memantine (5 mg) daily. Outcomes: The patient showed symptom improvement at his 3-month and 6-month follow-up appointments. Lessons: This patient may have a new type of mutation that is different from the one seen in cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy, although it involves a NOTCH3 defect. We propose that the entire NOTCH3 gene should be sequenced in patients with suspected hereditary VCI. This practice could facilitate the discovery of newpathogenic mutations and diseases.